Approach to Sustainability Assessment of Renewable Energy Technologies combining Fuzzy Logic with the Integrative Sustainability Triangle. Issue 1 (June 2016) - Bitter, Jan; Printz, Stephan; Lahl, Kristina; Vossen, René; Jeschke, Sabina
No abstract available